HUBUNGAN TINGKAT STRES DENGAN GANGGUAN INSOMNIA PADA MAHASISWA/MAHASISWI BIMBINGAN PENYULUHAN ISLAM SEMESTER DELAPAN TAHUN AKADEMIK 2019/2020 IAIN PONOROGO - arisma hardiyanti (ROSYADA: Islamic Guidance and Counseling, 2021)
This study aims to determine the level of stress and insomnia disorders experienced by BPI students in the eighth semester of the academic year 2019/2020 and to find out how stress levels relate to insomnia disorders. The variables in this study are free variables i.e. stress levels and bound variables i.e. insomnia disorders. The approach used in this study is a quantitative approach. Then the type of research is correlational. The sample used amounted to 53 respondents. The data collection technique uses questionnaires. Data analysis used using instrument tests (validity and reliability), statistical tests (descriptive statistics and inferential statistics), and contingency coefficient hypothesis tests. The results showed that the level of stress experienced by students of Islamic Counseling Guidance Semester Eight Academic Year 2019/2020 IAIN Ponorogo as many as 38 respondents (72%) moderate stress levels. Then insomnia disorder experienced by students / i Islamic Counseling Guidance Semester Eight Academic Year 2019/2020 IAIN Ponorogo as many as 43 respondents (82%) moderate level of insomnia. Based on hypothetical tests there is a significant relationship between stress levels and insomnia disorders at a significant level 5% r count = 0.479 > (greater) than r table = 0.266, then Ha accepted.Key word: stress, insomnia,